Annual Plan 1997-98 Volume-VIII Government of Assam - Planning Commission (Planning Commission, 1997)
From the 6th Plan period the Govt. of India has been placing very high priority on proper utilization of Non-Conventional Energy Sources. Particularly, to meet the energy needs of energy starved rural areas of the country in the centralized manner. Further, considering the physical problems and high cost involved in making available conventional energy like electricity of small isolated communities scattered over two hill districts of Assam De-Centralized energy systems based on to renewable energy resources is only answer to the energy problems of such areas. The is vast scope of using the small hill streams to generate both mechanical and electrical power to meet the- energy needs of small isolated villages. Solar photovoltaic electrifications is also a very potential source for electrifying isolated villages. At some hill tops and hill ridges there is good wind potential. There is ample scope of using biogas and animal wastes.
Government of Assam
Government of Assam
Keywords: Agriculture & Allied Village Activities; Rural development; Special Areas Programmes; Irrigation & Flood Control; Energy; Industry & Minerals Science Technology & Environment; Social Services; Village Industries under directorate; Industries Other That Village and Small Industries; Transmission and Distribution; Rural Electrification; Annual Plan For Hill Areas of Assam